Analyzing Speech Acts in Gritte Agatha's Podcast: 'Jadi Korban Bullying Satu Sekolah, Karena Peran Cinderella' - Nurjannah, Nurjannah; Saerudin, Sahur (Pusat Studi Gender dan Anak - PSGA (Center for Gender and Child Studies) Institut Agama Islam Negeri Lhokseumawe, Aceh, 2024)
ABSTRACT ENGLISH:Podcasts are an interesting type of YouTube content to discuss because there are numerous variations of speech acts in conversations between speakers and their speech partners. The goal of this study is to describe speech acts using locution, illocution, and perlocution from the Gritte Agatha Podcast